Criminal Policy Of The European Union And Ukraine: Issues And Prospects Of Rapprochement - Shepitko, Mykhaylo (Archives of Criminology and Forensic Sciences, 2022)
Ukraine’s path to the European Union through associated membership and receipt of candidate status opens new opportunities and adds additional responsibilities to Ukraine. Ukraine should implement a great number of reforms through democratization of its institutions, decentralization and digitalization. Major issues in this area are deemed to be corruption and weakness in implementing reforms in certain areas (justice, law enforcement, etc.). However, since the beginning of large-scale Russian war against Ukraine, the war that actually blocks but does not necessarily stop the process of Ukraine gradual transformation into a European state has become the main challenge. In this respect, emphasis should be made on the need to implement criminal law reform as part of European integration processes and to approach the criminal law of the European Union. As of today, the Working Group on Criminal Law Development of the Commission on Legal Reform under the President of Ukraine, which is engaged in development of a new Criminal Code of Ukraine, should pay attention to trends of European Union Criminal Law to formulate a relevant criminal legislation as a result of the ongoing reform.